2010
DOI: 10.13001/1081-3810.1366
|View full text |Cite
|
Sign up to set email alerts
|

Distance spectral radius of trees with fixed maximum degree

Abstract: Abstract. Distance energy is a newly introduced molecular graph-based analog of the total π-electron energy, and it is defined as the sum of the absolute eigenvalues of the molecular distance matrix. For trees and unicyclic graphs, distance energy is equal to the doubled value of the distance spectral radius. In this paper, we introduce a general transformation that increases the distance spectral radius and provide an alternative proof that the path Pn has the maximal distance spectral radius among trees on n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(40 citation statements)
references
References 17 publications
1
39
0
Order By: Relevance
“…Graphs with minimal and/or maximal distance spectral radius have been determined for various classes of graphs, see, e.g., [2,4,[6][7][8][9][10].…”
Section: The Distance Matrix Of G Is De Ned As D(g) = (Duv) Uv∈v(g) mentioning
confidence: 99%
“…Graphs with minimal and/or maximal distance spectral radius have been determined for various classes of graphs, see, e.g., [2,4,[6][7][8][9][10].…”
Section: The Distance Matrix Of G Is De Ned As D(g) = (Duv) Uv∈v(g) mentioning
confidence: 99%
“…As it turns out such problem has been partially solved a while ago by Ruzieh and Powers [9], who showed that the largest eigenvalue of the distance matrix of a connected graph G of order n is maximal if G is a path. The complete solution, however, was given more recently by Stevanović and Ilić [10]. [9,10].)…”
Section: Conjecture 2 the Largest Eigenvalue Of The Distance Signlesmentioning
confidence: 99%
“…Ruzieh and Powers [10] showed that the path P n is the unique n-vertex connected graph with maximal first distance eigenvalue, while the complete graph K n is the unique n-vertex connected graph with minimal first distance eigenvalue. Among others, Stevanović and Ilić [11] showed that the star S n is the unique n-vertex tree with minimal first distance eigenvalue. The extremal graphs with maximal or minimal first distance eigenvalues may be found in, e.g., [1,9,12,13,15].…”
Section: Introductionmentioning
confidence: 99%